Studies on the crystallization behavior of nylon-6 in the presence of layered silicates using variable temperature WAXS and FTIR - Nair, S. S.; Ramesh, C. (Macromolecules, 2005)
The crystallization of nylon-6 clay nanocomposite was studied by variable temperature wide-angle X-ray scattering (WAXS) and Fourier transform infrared spectroscopy (FTIR). Nylon-6 was found to crystallize into gamma phase at 210 degreesC, as indicated by its characteristic peaks in WAXS. However, an additional peak was observed close but on the lower angle side of the main gamma phase peak, indicating the presence of a metastable phase. The extent of metastable phase that developed was dictated by the clay content in the nanocomposite as well as the crystallization conditions. The temperature dependence of the d spacing of the gamma phase obtained in the presence of clay layers showed difference from the gamma phase obtained by treating nylon-6 in KI/I-2 solution. Variable temperature FTIR studies were conducted on the gamma phases for the first time, and it showed definite differences in the spectra of the phases obtained by the two methods.

Crystalline phases in nylon-11: studies using HTWAXS and HTFTIR - Nair, S. S.; Ramesh, C.; Tashiro, K. (Macromolecules, 2006)
Nylon-11 was crystallized into different crystalline phases by appropriate methods. The chance in the structure during heating was monitored in situ by wide-angle X-ray scattering (WAXS). The alpha phase obtained by precipitating nylon-11 in 1,4-butanediol started transforming into the pseudohexagonal phase on heating, but the transformation was not fully completed before melting. The melt crystallized sample at 175 degrees C gave the pseudohexagonal phase, which transformed into the alpha' phase on cooling to room temperature at about 100 degrees C. The d spacing of the 00 1 reflection also showed a change at the transition temperature. The melt-quenched sample showed the pseudohexagonal phase, which did not change during heating, but on cooling transformed into alpha' phase. The gamma phase was obtained by casting nylon-11 in trifluoroacetic acid (TFA), and it changed into the pscudohexagonal phase at about 110 degrees C on heating. The d spacing of the 001 reflection depended on the way in which it was obtained. The studies have shown that nylon-11 is one of the few nylons that exhibit an extensive degree of polymorphism. High-temperature Fourier transform infrared spectroscopy (HTFTIR) studies revealed, apart from the conformational differences between various phases of nylon-11, some information on the formation of the gamma phase.

Finite size effects on the structural and magnetic properties of sol-gel synthesized NiFe2O4 powders - George, M.; John, A. M.; Nair, S. S.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Magnetism and Magnetic Materials, 2006)
Nanoparticles of nickel ferrite have been synthesized by the sol-gel method and the effect of grain size oil its structural and magnetic properties have been Studied in detail. X-ray diffraction (XRD) studies revealed that all the samples are single phasic possessing the inverse spinel structure. Grain size of the sol-gel synthesized powders has been determined from the XRD data and the strain graph. A grain size of 9 nm was observed for the as prepared powders of NiFe2O4 obtained through the sol-gel method. It was also observed that strain was induced during the firing process. Magnetization measurements have been carried out on all the samples prepared in the present series. It was found that the specific magnetization of the nanosized NiFe2O4 powders was lower than that of the corresponding coarse-grained counterparts and decreased with a decrease in grain size. The coercivity of the sol-gel synthesized NiFe2O4 nanoparticles attained a maximum value when the grain size was 15 nm and then decreased as the grain size was increased further. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: grain size; magnetic properties; Nanoparticles; Nickel ferrite; strain